Controllable nanoscale engineering of vertically aligned MoS2 ultrathin nanosheets by nitrogen doping of 3D graphene hydrogel for improved electrocatalytic hydrogen evolution. (May 2017) - Zhao, Li; Hong, Congcong; Lin, Liangxu; Wu, Huaping; Su, Yewang; Zhang, Xiaobo; Liu, Aiping
Abstract: Three-dimensional (3D) porous molybdenum disulfide/nitrogen-doped reduced graphene oxide (MoS2 /N-rGO) hydrogels were fabricated through a facile and controllable one-pot hydrothermal method. The nanosized MoS2 ultrathin nanosheets were uniformly and vertically dispersed on the rGO framework after nitrogen incorporation. The incorporated nitrogen in rGO played a key role for nano-scaling of MoS2 due to the protonation at pyridinic N-doping sites on carbon surface. The vertically aligned edge of nanosized MoS2 sheets, nitrogen incorporation of rGO and 3D network structure made the MoS2 /N-rGO highly efficient for hydrogen evolution reaction, with improved double-layer capacitance and turnover frequency, small onset overpotential of 119 mV, low Tafel slope of 36 mV·decade −1 and superior long-time catalytic stability. Graphical abstract: